COMPLEX SYSTEM TACIT KNOWLEDGE EXTRACTION THROUGH A FORMAL METHOD. Issue 4 (28th December 2017) - Wajnberg, Mickael; Lezoche, Mario; Massé, Blondin Alexandre; Valtchev, Petko; Panetto, Hervé
ABSTRACT: A complex system integrates multiple sub‐systems and contains both knowledge in each sub‐system and in their connections. This paper aims to present the relational concept analysis as a method to extract "connection" knowledge as much as the sub‐system contained knowledge. A use case from neurology to validate the approach is introduced. A brain is a system that can be studied through different clinical examinations, therefore each clinical examination can be considered as a sub‐system.